Penerapan PSAK 24 (Revisi 2010) Atas Imbalan Kerja Perusahaan Go Public - Alfantoro, David Tri; Hastoni, Hastoni (Jurnal Ilmiah Akuntansi Kesatuan, 2014)
The purpose of this study was to determine how management policies in employee benefits and to determine whether the company's acoounting policies in accordance with PSAK 24 (Revised 2010). Object of this study is Going Public Companies that have adopted PSAK 24 (Revised 2010). The results of this study indicate that the studied Go Public Company has applied the kinds of employee benefits. Ten go public companies examined authors have implemented employee benefits in accordance with SFAS no. 24 (revised 2010). The elements of employee benefits which the company has applied by these ten companies are post-employment health care benefits, pension benefits, other long-term post-employment benefits. Ten go public traded companies studied have presented losses/gains actuarial using OCI approach at the statement of comprehensive income. The ten go public companies have the largest amount of the loss/gain actuarial is PT Bukit Asamfor (Rp 879.288 billion), while the public company that has implemented a post-employment medical benefits is PT Bukit Asam and PT Vale Indonesia. Companies that have largest amount of a long-term post-employment benefit liabilities is PT Astra International with Rp 2.741 billion. There is one company that use foreign currency (US Dollar) is PT Vale Indonesia. Key words: Employee Benefits